PENGARUH PENYALAHGUNAAN TEKNOLOGI INFORMASI DAN INTEGRITAS MAHASISWA TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI SEBAGAI CALON AKUNTAN (Studi kasus Mahasiswa akuntansi Universitas Islam Swasta Di Kota Medan) - Heny Triastuti Kurnia Ningsih; Adella Oktaviani Simbolon (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
This study aims to analyze the effect Of Information Technology Misuse and Student Integrity Towards Academic Fraud Behavior Of Accounting Students As Prospective Accountant at Islamic Private Universities in Medan. The research data was obtained from questionnaires by looking for samples using Slovin Technique. Data collection techniques use Library Research and Field Research. The data analysis technique used is Descriptive Statistics Analysis, Data Trend, Validity Test, Reliability Test, Classical Assumption Test, Quantitative Analysis, T Test, F Test and Determination Test. The type of research used is Descriptive Analysis Technique using SPSS version 15. The results of the study are: 1) There is no significant effect of Information Technology Misuse towards academic fraud behavior of accounting students as prospective accountant. 2) There is a significant effect of integrity student towards academic fraud behavior of accounting students as Prospective accountant. 3) There is a  significant effect of Information Technology Misuse and Student Integrity towards academic fraud behavior of accounting students as prospective accountant